THE SIGNIFICANCE OF THEOLINGUISTIC INQUIRIES AND THEORETICAL FRAMEWORKS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The exploration and theoretical underpinnings of theolinguistics are deeply significant within academic discussions, providing valuable perspectives at the crossroads of theology and linguistics. This paper explores the importance of theolinguistic investigations, clarifying their contribution to the comprehension of religious texts, linguistic frameworks, and cultural intricacies. By conducting an extensive review of existing literature and empirical analysis, this study emphasizes the varied methodologies utilized in theolinguistic inquiry, presenting convincing findings that emphasize its academic significance.